Characteristics of vomiting as a predictor of intracranial injury in pediatric minor head injury. Issue 6 (November 2020) - Harper, Jessica A.; Klassen, Terry P.; Balshaw, Robert; Dyck, Justin; Osmond, Martin H.; ,
ABSTRACT: Objectives: Vomiting is common in children after minor head injury. In previous research, isolated vomiting was not a significant predictor of intracranial injury after minor head injury; however, the significance of recurrent vomiting is unclear. This study aimed to determine the value of recurrent vomiting in predicting intracranial injury after pediatric minor head injury. Methods: This secondary analysis of the CATCH2 prospective multicenter cohort study included participants (0–16 years) who presented to a pediatric emergency department (ED) within 24 hours of a minor head injury. ED physicians completed standardized clinical assessments. Recurrent vomiting was defined as ≥ four episodes. Intracranial injury was defined as acute intracranial injury on computed tomography scan. Predictors were examined using chi-squared tests and logistic regression models. Results: A total of 855 (21.1%) of the 4, 054 CATCH2 participants had recurrent vomiting, 197 (4.9%) had intracranial injury, and 23 (0.6%) required neurosurgical intervention. Children with recurrent vomiting were significantly more likely to have intracranial injury (odds ratio [OR], 2.3; 95% confidence interval [CI], 1.7–3.1), and require neurosurgical intervention (OR, 3.5; 95% CI, 1.5–7.9). Recurrent vomiting remained a significant predictor of intracranial injury (OR, 2.8; 95% CI, 1.9–3.9) when controlling for other CATCH2 criteria. The probability of intracranial injury increased with number of vomiting episodes, especially when accompanied by other high-risk factors, including signs of a skull fracture, or irritability and Glasgow Coma Scale score < 15 at 2 hours postinjury. Timing of first vomiting episode, and age were not significant predictors. Conclusions: Recurrent vomiting (≥ four episodes) was a significant risk factor for intracranial injury in children after minor head injury. The probability of intracranial injury increased with the number of vomiting episodes and if accompanied by other high-risk factors, such as signs of a skull fracture or altered level of consciousness.